Senescence-like phenotype in post-mitotic cells of mice entering middle age - Raffaele, Marco; Kovacovicova, Kristina; Bonomini, Francesca; Rezzani, Rita; Frohlich, Jan; Vinciguerra, Manlio (Aging (Albany, NY. Online), 2020)
Staining mice tissues for β-galactosidase activity is a fundamental tool to detect age- or disease-associated cellular senescence. However, reported analyses of positivity for senescence-associated β-galactosidase activity or for other markers of senescence in post-mitotic cells of healthy murine tissues have been fragmentary or inconclusive. Here, we attempted to independently deepen this knowledge using multiple senescence markers within the same cells of wild type mice entering middle age (9 months of age). A histochemistry protocol for the pH-dependent detection of β-galactosidase activity in several tissues was used. At pH 6, routinely utilized to detect senescence-associated β-galactosidase activity, only specific cellular populations in the mouse body (including Purkinje cells and choroid plexus in the central nervous system) were detected as strongly positive for β-galactosidase activity. These post-mitotic cells were also positive for other established markers of senescence (p16, p21 and DPP4), detected by immunofluorescence, confirming a potential senescent phenotype. These data might contribute to understanding the functional relation between the senescence-associated β-galactosidase activity and senescence markers in post-mitotic cells in absence of disease or advanced aging.
Keywords: Animals; biologické markery; beta-galaktosidasa; Hydrogen-Ion Concentration; Biomarkers; Aging; Immunohistochemistry; stárnutí buněk; Mice; myši; imunohistochemie; Mitosis; mitóza; beta-Galactosidase; stárnutí; zvířata; Mice, Inbred C57BL; koncentrace vodíkových iontů; Cellular Senescence; myši inbrední C57BL